Earth - Daily, Robert (New York : Watts, 1994)
Photographs and text discuss the history of the earth, what the earth is composed of, and life on earth.
Includes bibliographical references (p. 61), index, and glossary.
Booklist.
Library Talk.
Wilson's Junior High School.
5.7
4-6
Keywords: Earth -- Juvenile literature; Earth; Earth